Stability assessment for rhizome yield and its constituent characteristics in various genotypes of turmeric - Chitra , R; Kalaiyarasi, R (Bangladesh Journal of Botany, 2024)
Turmeric is an important rhizomatous spice as well as medicinal plant with the wide genetic variability with regard to growth and yield that thrives well at lower altitudes to higher elevations up to 1600 m above MSL and also under rainfed conditions. Stability analysis was done in 55 turmeric genotypes, including three check varieties, during 2016-17 and 2020-21 at Tamil Nadu Agricultural University, Coimbatore, with per se performance. The joint regression analysis revealed no significant difference among various genotypes, indicating the uniformity of the genotypes. However, the G x E (linear) interaction was significant for three out of five traits studied, revealing the profound influence of environment on phenotypes. Based on individual parameter’s of stability (xi bi and S2 di), genotypes CL 2 and CL 100 were found stable in performance over the years. Further 32 genotypes were found to have significantly higher regression coefficients along with mean values above the general mean for fresh rhizome yield, depicting the scope for improved performance under favourable farming conditions. Based on the mean performance, regression coefficient, and deviation from regression values, it was found that the stability of yield was imparted in the genotypes, viz., CL 100, CL 122, CL 147, CL 213, and CL 269, through the stable performance of major yield- contributing traits like number of leaves per plant, number of tillers per plant, and rhizome yield per plant. These genotypes may be useful genetic resources for the development of high- yielding, stable varieties of turmeric. Bangladesh J. Bot. 53(4): 1027-1033, 2024 (December)